Childhood interstitial lung disease survivors in adulthood: a European collaborative study - Manali, Effrosyni D; Griese, Matthias; Nathan, Nadia; Uzunhan, Yurdagül; Borie, Raphael; Michel, Katarzyna; Schwerk, Nicolaus; Fijolek, Justyna; Radzikowska, Elżbieta; Chua, Felix; Pabary, Rishi; Mogulkoc, Nesrin; et al. (The European respiratory journal, 2025)
BACKGROUND: Interstitial lung disease is rarer in children than adults, but, with increasing diagnostic awareness, more cases are being discovered. The prognosis of childhood interstitial lung disease is often poor, but increasing numbers are now surviving into adulthood. AIM: To characterise childhood interstitial lung disease survivors and identify their impact on adult interstitial lung disease centres. METHODS: This was a European study (34 adult and childhood interstitial lung disease centres) reporting incident/prevalent cases of childhood interstitial lung disease survivors from January to July 2023. Epidemiological, clinical, physiological and genetic data were collected. RESULTS: 244 patients were identified with a median (interquartile range) age at diagnosis of 12.5 years (6-16 years) and age at study inclusion of 25 years (22-33 years), with 51% male, 86% nonsmokers and a median (interquartile range) % predicted forced vital capacity of 70% (47-89%) and diffusing capacity of the lungs for carbon monoxide of 48% (32-75%). 32% were prescribed long-term oxygen and 227 (93%) were followed up in adult centres whereas 17 (7%) never transitioned. The commonest diagnoses (82%) were childhood interstitial lung disease category B1 (sarcoidosis, hemosiderosis, connective tissue disorders, vasculitis) at 35%, A4 (surfactant-related) at 21%, B2 (bronchiolitis obliterans, hypersensitivity pneumonitis) at 14% and Bz (unclassified interstitial lung disease) at 13%. Bz patients had the worst functional status. 60% of all patients were still being prescribed corticosteroids. Re-specification of diagnosis and treatment were made after transition for 9.8% and 16% of patients, respectively. Not all childhood interstitial lung disease diagnoses were recognised in adult interstitial lung disease classifications. CONCLUSION: Childhood interstitial lung disease survivors are seen in most adult interstitial lung disease centres and only a minority continue follow-up in paediatric centres. Survivors have a significant loss of lung function. The heterogeneity of their aetiologies and therapeutic requirements has a real impact on adult interstitial lung disease centres. Re-specification of diagnosis and treatment may contribute to precision and personalisation of management.
Keywords: Humans; přežívající; dítě; Child; Female; mladý dospělý; dospělí; intersticiální plicní nemoci; Survivors; lidé; Europe; Adult; ženské pohlaví; Male; Adolescent; prognóza; Young Adult; Lung Diseases, Interstitial; Prognosis; mužské pohlaví; Evropa; mladiství